Study of the thermal properties of clays from the Krasnoyarsk and Sukpak deposits of Tuva - Kopylov, N.I.; Solotchina, E.P. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The most important factor in the development of industry and the construction industry of individual and hard-to-reach regions is the availability of their respective raw materials and energy base. Their possible effective use can often be difficult due to difficult geological conditions, lack of required transport connections and removal from industrial centers. So, in particular, more than a dozen industrial deposits of fossil raw materials and clay rocks located in hard-to-reach areas are known on the territory of the Republic of Tuva and their extraction is currently not cost-effective. Therefore, available low-grade raw materials with the introduction of various additional components can be used as the main raw material. The latter requires a certain amount of complex research, namely, the study of the dynamics of the behavior of the initial components, their mixtures, the batching compositions during roasting, the development of technology parameters using new raw materials, etc. In this connection, in the first stage of the research in this paper using a number of methods of physicochemical analysis the dynamics of the phase transformations occurring in the material of the rare-earth clays of the Sukpak and Krasnoyarsk deposits of Tuva is studied, with their heating in the temperature range up to ~ 1020–1025 °C. As a result, the stages of successive thermal decomposition of the material were determined, namely, the removal of sorption and hydrated moisture, the destruction of hydroaluminosilicates, the decomposition of magnesian calcite, and the initial formation of high-temperature aluminosilicate structures.
Туваның Сукпак жəне Красноярск кен орындары топырақтарының термиялық қасиеттерін зерттеу
Изучение термических свойств глин Сукпакского и Красноярского месторождений Тувы
Keywords: thermal; X-ray phase analysis; X-ray fluorescent analysis; clays; oxides; carbonates; silicates; aluminosilicates